SUSTAINABLE SERVICE DELIVERY MODEL: ECOLOGICAL, ECONOMIC, AND SOCIAL DIMENSIONS - Soy , Marina; Kamolov , Dostonbek (Effective scientific journals, 2025)
The shift toward sustainable development has transformed service industries across the globe, pushing organizations to integrate ecological, economic, and social considerations into their business models. This article examines the sustainable service delivery model by analyzing three interrelated pillars: environmental responsibility, economic efficiency, and social well-being. The study evaluates theoretical foundations, contemporary innovations, and global best practices, and proposes a holistic conceptual model suitable for modern service sectors such as tourism, hospitality, transportation, healthcare, and public services. Findings suggest that sustainable service delivery requires systemic innovation, digital transformation, responsible resource management, and stakeholder engagement. The research concludes that the successful transition to sustainability in service industries enhances competitiveness, reduces long-term operational risks, and strengthens customer trust.